Utilizing Novel Modular Static Synchronous Series Compensators for Increased RES Integration and Cross-Border Power Flows - Konstantinos F. Krommydas; Christos-Spyridon G. Karavas; Konstantinos A. Plakas; Edward Hanlon; Efthimia Chassioti; Ioannis Moraitis (IEEE Open Access Journal of Power and Energy)
Developing innovative technologies is considered a critical enabler to successfully integrate large amounts of renewable generation and ensure the stable operation of power systems. In this paper, we propose a novel modular static synchronous series compensator (M-SSSC) that can adjust transmission line reactance in real-time in order to change network power flows. For the first time, a detailed demonstration in a real transmission system is presented that shows how such an innovative technology can maximize overall network utilization and manage operational constraints. Usually, only power flow simulations studies are presented that inevitably contain model inaccuracies and design assumptions. By exploiting the concepts of correlation coefficient and linear regression we demonstrate how the M-SSSC can facilitate renewable generation and cross-border power flows. A comparison with other innovative technologies such as phase shifting transformers, unified power flow controllers and dynamic line rating systems is presented. It is showcased that the proposed technology can be a suitable economical solution when distributed impedance control is needed, has a smaller footprint per ohm impedance, and depicts various advantages, such as rapid deployability, scalability and redeployability compared to other technologies. Furthermore, the M-SSSC can offer real-time, granular control and coordination between multiple deployments is possible, to optimize system power flows.